Implementation of Regulation of the Minister of Law and Human Rights Number 2 of 2019 concerning the Resolution of Disharmony of Laws and Regulations through Mediation Against the Examination of Laws and Regulations in Indonesia - Tundjung Herning Sitabuana; Jeane Neltje Saly; Rasji Rasji; Nada Dwi Azhari (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The disharmony of legislation occurs because of the existing of the selfishness at ministry/institution sector in the planning process the creation of law. The hierarchy of legislation aims to determine its own degrees in order to create the harmonic legislation system. In fact, the contradiction inter legislation still becomes one of the legal issues in Indonesia which never been closed. The other problems are many dispute resolutions of legislation not infrequently a rule under the legislation whom it must be sourced from. The existence of the regulation from Ministry of Law and Human Rights No. 2 in 2019 about the disharmony resolution of legislation is assumed as a change effort in seeking an alternative resolution out of the court if the norm conflicts happen inter legislation. This mediation comes out as an answer because of not satisfaction with dispute resolution in court that takes a long time, needs much money the decision which is resulted by the court often make dissatisfaction for the parties. They cause a case, namely how is the authority of the Ministry of Law and Human Rights in resolving the disharmony of legislation through mediation based on its legislation? The method which is used in this research is normative legal. The result shows that the mediation gives new hopes for new institutions in resolving a dispute of legislation in Indonesia. However; the delegation of ministerial regulation should be given some clear limitations to avoid overlapping rules, so it doesnâ€™t bring confusion in its implementation.Â